Editorial - Zanotelli, Claudio (Geografares, 2020)
In this issue commemorating the 20th anniversary of Geografares, we rescued three important moments for the magazine. Right at the beginning, the interview with Yves Lacoste published in three parts in the first three issues, the interview with Manuel Correa de Andrade carried out in 2000 and published in number 2 in 2001 and the publication, also in the second issue of Geografares, of an article originated from a lecture given at UFES by Antonio Carlos Robert de Moraes and entitled "Bases da formação territorial do Brasil [Bases of territorial formation in Brazil]".This issue also brings several articles on topics related to Geography in different perspectives of knowledge.